STRATEGIES IN REDUCING AHMAD DAHLAN STUDENTS’ ANXIETY IN SPEAKING - Megawati Basri; Balqis Husain; Fahmi Djaguna (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2020)
The study aims to find out the strategies or ways of reducing student anxiety in speaking English. There are six selected students based on observation results to be interviewed. This research is done by a qualitative method with a descriptive approach. The results of this study show that following the English community, avoiding eye contact with friends or lecturers, confident, relaxing, and relaxed and often practicing for individual participants can reduce student anxiety in English speaking.